Transferred : How to Add Original Images to Everything From Fabrics to Ceramics - Cordova, Isabel de (London Conran Octopus Ltd., 2001)
Transferring images is a simple decorative technique. Any image that can be colour photocopied or scanned can be transferred, using the heat of an iron, onto a variety of surfaces from fabrics, metals and plastics, through to cardboard, plaster and glass. This book shows how.
Include Color Illustration and Index.
How to Add Original Images to Everything From Fabrics to Ceramics.
Keywords: Transfer-printing